Arabic Writing Skills and the Imla’ Method: A Systematic Review of Dictation Pedagogy in Language Learning - Feni Zumara; Mukhlisah Mukhlisah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Arabic writing proficiency (maharah kitabah) remains a persistent challenge in second language acquisition due to the intricate cognitive demands of orthographic accuracy, morphological arrangement, and syntactic rules. While dictation (imla’) is traditionally utilized to mitigate these difficulties, a comprehensive synthesis of its empirical efficacy across varying educational tiers remains scarce. This systematic literature review evaluates the pedagogical impact and structural outcomes of implementing the imla’ method to enhance Arabic writing skills. Adopting a rigorous methodology, this study synthesized empirical literature indexed in major academic databases between 2021 and 2025. The thematic synthesis reveals that imla’ strategies exert a robust positive effect on maharah kitabah. Specifically, imla’ masmu’ (auditory dictation) and imla’ ikhtibari (test dictation) significantly enhance phoneme-to-grapheme mapping, sentence structure accuracy, and orthographic error reduction, while concurrently bolstering auditory working memory. Furthermore, the review identifies that the optimization of this method is heavily contingent upon strategic teacher scaffolding, sustained longitudinal practice, and learners' prior vocabulary thresholds. Crucially, the data reveals that basic orthographic errors remain stubborn and persist into secondary education if left uncorrected early on. These insights provide a critical framework for educators, implying that imla’ should be systematically integrated into modern Arabic curricula as a foundational, cognitively grounded pedagogical tool rather than a passive assessment mechanism.